Model Pembelajaran Literasi Musik Pentatonis China Pada Siswa Kelas 3 Di Sd Santo Aloysius Batununggal Bandung - Reyhan Swarna Medica; Uus Karwati (Jurnal Impresi Indonesia, 2025)
This study aims to develop and evaluate a Chinese pentatonic-based music literacy learning model applied to third-grade students at SD Santo Aloysius Batununggal Bandung. The model is designed to address challenges in reading musical notation and to introduce students to their ancestral Chinese musical heritage. Employing an evaluation approach and mixed methods, the research involved the creation of instructional videos integrated into the LMS Scola e-learning platform. Results showed that this model significantly improved students’ ability to read and write musical notation and to understand the Chinese pentatonic scale. The learning process became more engaging and interactive through the use of video, animation, hand signs, and traditional Chinese music. However, there were some drawbacks, such as the need for tempo adjustments and additional support for students with lower achievement. Overall, the model is effective and offers an innovative solution for music education at the elementary level.